2018
DOI: 10.1371/journal.pone.0196405
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin attenuates lipopolysaccharide-induced acute lung injury by controlling the Nrf2 pathway

Abstract: BackgroundA major feature of acute lung injury (ALI) is excessive inflammation in the lung. Vitexin is an active component from medicinal plants which has antioxidant and anti-inflammatory activities. Oxidative stress and inflammation play important roles in the pathophysiological processes in ALI. In the current study, we investigate the effect and potential mechanisms of Vitexin on lipopolysaccharide (LPS)-induced ALI.MethodsALI was induced by LPS intratracheal instillation in C57BL/6 wild-type mice and Nrf2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Deficiency of NRF2 signaling leads to severe lung injury of mice in response to LPS exposure [38]. In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42].…”
Section: Discussionsupporting
confidence: 90%
“…Deficiency of NRF2 signaling leads to severe lung injury of mice in response to LPS exposure [38]. In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42].…”
Section: Discussionsupporting
confidence: 90%
“…Vitexin attenuated RANKL-induced activation of MAPK signal pathways and NF-κB signaling pathways [51]. Also, the activation of Nrf2/HO-1 pathway is one of the mechanisms of vitexin to limit inflammation in a model of LPS-induced acute lung injury [52]. It was demonstrated by Chen et al, [114] in isoflurane-treated PC12 cells that vitexin is neuroprotective by downregulating the expression of TRPV1 and glutamate ionotropic receptor NMDA type subunit 2B (NR2B) protein expression.…”
Section: Flavonesmentioning
confidence: 98%
“…The red arrows represent endogenous pathways that are inhibited by flavonoids resulting in reduced pain and inflammation. , NF-κB [51] and Nrf2 [52], Quercetin: MAPK [53], NF-κB [53][54][55], AKT [56], Nrf2 [33,54], and NLRP3 [57] and Naringenin: NF-κB [58][59][60] and Nrf2 [59,61,62]. (B) Ion channels expressed by neurons that are targeted by Vitexin, Quercetin, and Naringenin to reduce pain.…”
Section: Pre-clinical Evidence Of Flavonoids For Pain Controlmentioning
confidence: 99%
“…Oxidative stress is characterized by the overproduction of ROS and it plays an important role in the pathogenesis of ALI [13]. ROS accumulation aggravates the inflammatory responses by promoting the expression of proinflammatory cytokines, and infiltration of inflammatory cells, leading to ALI [15,16]. In our study, SP treatment displayed a potent DPPH radical-scavenging activity and suppressed ROS generation in TNF-α-stimulated NCI-H292 cells.…”
Section: Discussionmentioning
confidence: 48%
“…Oxidative stress also plays a major role in the pathogenesis of lung injury in LPS-induced ALI [14,15]. Nuclear factor erythroid-2 related factor 2 (Nrf2) is a redox-sensitive transcription factor and it regulates the antioxidant and detoxifying enzymes [16]. It has been reported that Nrf2 plays an essential role in protecting cells against inflammatory and oxidative stress-mediated diseases [17,18].…”
Section: Introductionmentioning
confidence: 99%